Code-Switching and Translanguaging in Formative Assessment: Supporting ELT Development - Pillay, Preya (Universitas Pendidikan Mandalika, 2025)
The implementation of English as the medium of instruction from Grade 4 in South African schools has necessitated that teachers explore effective strategies to support learners transitioning from mother tongue instruction, particularly through formative assessment practices. It is with this background in mind that this qualitative study aimed at gaining deeper insights into teachers' use of code-switching and translanguaging strategies to support Grade 4 learners' English language development through formative assessment in three Gauteng township schools. Data were collected through in-depth interviews with 6 English teachers and classroom observations. The accumulated data were integrated and analysed thematically according to Braun and Clarke's (2006) approach. The findings of the study indicate that teachers' application of code-switching and translanguaging in English lessons, particularly during oral questioning, feedback provision, and vocabulary explanation in formative assessment, contributed significantly to learners' comprehension and engagement in English language learning. However, challenges such as lack of formal training in multilingual assessment practices and pressure to prepare students for English-only summative assessments were also identified. The study concludes that effective formative assessment in Grade 4 English classrooms could be enhanced through the strategic use of learners' full linguistic repertoires and the integration of multilingual practices into English language teaching and assessment policies.